INSTITUTIONAL PROBLEMS IN THE IMPLEMENTATION OF SCIENTIFIC-LEGAL RECOMMENDATIONS IN THE FIELD OF PUBLIC ADMINISTRATION (Universal International Scientific Journal, 2026)
This article analyzes the institutional problems that arise in the process ofimplementing scientific and legal recommendations into practice within the public administrationsystem
Keywords: public administration; scientific-legal recommendations; institutional reforms